Enhanced Results in Common and Coincidence FixedPoint Theory with Applications to Simulation Mappings (European Journal of Pure and Applied Mathematics, 2024)
In this manuscript, we apply the simulation mappings to present and verify several original results of common and coincidence fixed point in complete S-metric spaces. Moreover, using S-metric to expand and generalized diverse results in the literature involving simulation mappings. On the other hand, we apply our major results to derive several common and coincidencefixed point theorems for right monotone simulation map in complete S-metric. As implementations, various related outcomes of fixed-point theory via specific simulation mappings are obtained in complete S-metric spaces. Additionally, illustrative examples and some applications to solve an integral equation are introduced to support our major results.
Keywords: ${S}$-metric spaces, simulation mappings, common and coincidence fixed points, symmetrical complete ${S}$-metric